2017
DOI: 10.3390/su9112121
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility as a Strategic Means to Attract Foreign Investment: Evidence from Korea

Abstract: This study examines how foreign investment can be driven by corporate social responsibility (CSR). By specifying the underlying mechanism of foreign investors' stock picking behavior, we argue that CSR can attract foreign investment. Given that CSR actions are taken to meet various needs of its stakeholders, the host firm can convey a reliable signal to foreign investors as well as the stakeholders. As such, foreign investments can be increased in the host firm. This idea is examined in a sample of Korean firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
2
15
1
Order By: Relevance
“…Oh et al [29] employed a sample of 118 large Korean firms and found a significant and positive relationship between CSR ratings and ownership of institutions (which are under strong influence of the Korean government). However, Oh et al [29] also found foreign invested firms have relatively high CSR ratings and this result was confirmed by Lee et al [30] who conducted a study using panel data of the Korea Economic Justice Institute (KEJI) Index and found a positive correlation between CSR performance and foreign ownership.…”
Section: Ownership Size Slack Resources and Sustainabilitymentioning
confidence: 74%
“…Oh et al [29] employed a sample of 118 large Korean firms and found a significant and positive relationship between CSR ratings and ownership of institutions (which are under strong influence of the Korean government). However, Oh et al [29] also found foreign invested firms have relatively high CSR ratings and this result was confirmed by Lee et al [30] who conducted a study using panel data of the Korea Economic Justice Institute (KEJI) Index and found a positive correlation between CSR performance and foreign ownership.…”
Section: Ownership Size Slack Resources and Sustainabilitymentioning
confidence: 74%
“…A company with growth potential can be more active in CSR activities, which predicts a positive correlation between the market value ratio to book value (MB) and CSR activities [41]. Previous studies have shown a positive relationship between CSR and foreign ownership [43]. The higher the foreign ownership (FOR), the more CSR is expected to increase.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Based on customer behaviour, businesses then analyse customers habits, ways of preferred presentation and taste. Entrepreneurship through customer care is part of modern business strategy textbooks, where online is no longer only recommended, but rather required [7]. At the end of 2019, it was inconceivable that bricks and mortar stores could be temporarily closed by the state.…”
Section: Introductionmentioning
confidence: 99%